The Image of a TV Journalist and the Requirements for a Reality Show Host (Herald of Journalism, 2022)
The article discusses the image of a TV journalist, evaluates the professional level of reality show hosts, analyzes typical shortcomings, and lists and classifies the requirements for reality show hosts on the part of professional ethics and television standards. The goal is to substantiate theoretically the professional and creative factors that form the image of a TV journalist. As a result of the research it will be possible to evaluate the professionalism and analyze typical shortcomings of the reality show’s hosts on domestic television. The idea is to form a TV journalist school by substantiating the ethical standards and professional rules for the image of a TV journalist in the country. The scientific and practical significance lies in the fact that in modern society domestic television specialists do not follow the rules of linguistics, do not master the psycholinguistic aspects of speech culture, make mistakes on the air etc. Therefore, this study is aimed to establish the professional rules of the domestic school of TV presenters. Research methods: analysis, comparison, generalization, review and justification.The expected result is the substantiation of professional principles for eliminating typical shortcomings by analyzing scientific opinions about the image of a TV journalist in the domestic information space. Presentation of the draft rules of the culture of national television broadcasting within the framework of the domestic television standard. Research value: the article is based on the scientific works of Kazakhstani and foreign scientists who analyzed the image of TV journalists. Therefore, the facts and conclusions of the article can be the basis for analyzing the level of development of modern television journalism in Kazakhstan. Key words: announcer’s image, television criticism, television phenomenon, reality image, reality mode.